Length-weight relationship and relative condition factor (Kn) of freshwater spiny eel, Mastacembalus armatus (Lacepede) from Mymensingh, Bangladesh - Narejo, N T; Rahmatullah, S M; Rashid, M Mamnur (Indian Journal of Fisheries, 2011)
The length- weight relationship, relative condition factor (Kn) and morphometric and meristic counts of the fresh water spiny eel, Mastacembalus armatus (Lacepede) from District Mymensingh, Bangladesh were studied by examination of 217 specimens collected between March 2000 to October 2000. These fishes ranged from 14.8- 47.5 cm in total length and 8.0- 139.4 g in weight. The relation between the total length and weight of M. armatus is described as LogW= - 2.30 + 2.72 ´ Log L for males, Log W= -2.1 + 2.60 ´ Log L for females and Log W= - 2.38 + 2.78 ´ Log L for sexes combined. The mean relative condition factor (Kn) values ranged from 0.83 to 1.31 for males, 0.80 to 1.29 for females and 0.76 to 1.30 for combined sexes. The morphometric measurements of various body parts and meristic counts were recorded for males and females separately. Application of Z test showed no significant morphological difference between two sexes and the relationship between body measurements was found to be linear. The length- weight relationship and relative condition factor showthat the growth of M. armatus is quite satisfactory.